Antiproliferative and Apoptotic Effects of Sesbania grandiflora Leaves in Human Cancer Cells - Pajaniradje, Sankar (Hindawi Publishing Corporation, 2014)
Natural phytochemicals and their derivatives are good drug candidates for anticancer therapeutic approaches against multiple targets. We report here the initial findings from our studies on the anticancer properties of the leaves of the medicinal plant Sesbania grandiflora. In the current study, five different solvent fractions from the leaves of S. grandiflora were tested on cancer cell lines such as MCF-7, HepG2, Hep-2, HCT-15, and A549. The methanolic fraction of S. grandiflora was found to exert potent antiproliferative effects especially in the human lung cancer cell line, A549. Caspase 3 was activated in the methanolic fraction treated A549 cells thereby leading to cell death by apoptosis. DAPI staining, DNA laddering, and decrease in mitochondrial membrane potential further confirmed the apoptotic mode of cell death. The high levels of ROS intermediates as evidenced by DCF-DA staining could have played a role in the apoptotic induction. Decrease in levels of cyclin D1 and decrease in the activation of NFkB were observed in A549 cells on treatment with methanolic fraction, giving a hint on the possible mechanism of action. These results prove that the medicinal plant S. grandiflora can be explored further for promising candidate molecules to combat cancer, especially lung cancer.